2012
DOI: 10.1177/0148607111430087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prebiotic‐Containing Infant Formula on Gastrointestinal Tolerance and Fecal Microbiota in a Randomized Controlled Trial

Abstract: Infant formula containing the studied oligosaccharides was well tolerated, increased abundance and proportion of bifidobacteria, and reduced fecal pH in healthy infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 51 publications
(95 reference statements)
7
67
0
Order By: Relevance
“…20 The addition of the prebiotic GOS/FOS mixture to an infant formula was proven to have a stimulating effect on the growth of bifido 21 and feces from infants fed a GOS/GOS mixture had a higher absolute number (P D 0.0083) and proportion (P D 0.0219) of bifido, very similar to breastfed infants. 22 An intervention of 26 weeks with 6 g/L scGOS and lcFOS (ratio 9:1) resulted in increased percentages of bifido in the supplemented group (60.4%) compared to the control group (52.6%, P D 0.04). The percentages of Clostridium spp.…”
Section: Prebiotics Gut Metabolic Activity and Bifidogenic Effectmentioning
confidence: 94%
See 1 more Smart Citation
“…20 The addition of the prebiotic GOS/FOS mixture to an infant formula was proven to have a stimulating effect on the growth of bifido 21 and feces from infants fed a GOS/GOS mixture had a higher absolute number (P D 0.0083) and proportion (P D 0.0219) of bifido, very similar to breastfed infants. 22 An intervention of 26 weeks with 6 g/L scGOS and lcFOS (ratio 9:1) resulted in increased percentages of bifido in the supplemented group (60.4%) compared to the control group (52.6%, P D 0.04). The percentages of Clostridium spp.…”
Section: Prebiotics Gut Metabolic Activity and Bifidogenic Effectmentioning
confidence: 94%
“…27 Fecal pH was lower (P D 0.01) in breastfed and prebiotic-formula fed infants than with standard infant formula. 22 A low level of GOS (0.24 g/100 mL) in infant formula brings the fecal pH to the same level as with human milk. 17 In a recent, large trial including 365 infants receiving GOS up to the age of 1 year, fecal pH was decreased.…”
Section: Prebiotics and Fecal Phmentioning
confidence: 99%
“…The results showed that OFS supplementation decreased serum ALT and AST levels significantly compared to that in placebo group. Prebiotics of mixed galacto-oligosaccharides and fructo-oligosaccharides (9:1) also showed stimulating effect on abundance of Bifidobacteria bacteria in infants [132]. Similarly, administration of prebiotic inulin and oligofructose (50:50 in mixture) increased abundance of Bifidobacterium and Faecalibacterium prausnitzii, which negatively correlated with serum LPS levels [133].…”
Section: Gut Microbiota-targeted Therapy With Prebioticmentioning
confidence: 89%
“…Increasing abundance and proportion of bifidobacteria Formula-fed infants (FF) [132] ITF prebiotics (inulin+oligofru ctose) …”
Section: Probiotic Mixturesmentioning
confidence: 99%
“…mesenteric lymph nodes (mainly answer to the commensal stimulus of benefic bacteria for healthy status, characterized by the development of tolerance in the intestinal epithelium. The activation capacity of the immune system by prebiotics is related to a modulatory effect on the gut flora (HOLSCHER et al, 2012) and to stimulation of the immune system via different mechanisms of action NÖRNBERG, 2003).…”
Section: Crypt (µMmentioning
confidence: 99%